Effect of Process Parameters on Hydrogen Production and Efficiency in Biomass Steam Gasification with in-situ CO2 Capture - Inayat, Abrar; Ahmad, Murni M; Abdul Mutalib, M I; Yusup, Suzana (2010)
Hydrogen is considered as an attractive clean fuel for the future. Hydrogen production via biomass steam gasification with CO2 adsorption is receiving attention due to its sustainability. The paper reports on the impact of temperature, steam/biomass ratio and sorbent/biomass ratio on hydrogen production performance in a steam gasification process using a simulation model developed in MATLAB. The model is used to predict the product gas composition, hydrogen yield and thermodynamic efficiency of the process. It was observed that with the increased in temperature and steam/biomass ratio, the hydrogen concentration and yield also increase but the thermodynamic efficiency decreases. Among the process parameters, the steam feed rate was found to have the most impact on the hydrogen production and the thermodynamic efficiency. At 950 K with steam/biomass ratio of 3.5 and sorbent/biomass ratio of 1.0, a maximum hydrogen concentration of 0.82 mole fraction is obtained in the product gas. Hydrogen yield increases from 78 to 97 g/kg of biomass with the increase in temperature from 800 to 1300 K and in steam/biomass ratio from 2.0 to 5.0. Maximum hydrogen efficiency i.e. at 87% is observed at 800 K and steam/biomass ratio of 2.0. At sorbent/biomass of 1.52, hydrogen purity is predicted to reach 0.98 mole fraction with CO2 present in system absorbed.